Pengaruh Penambahan Daging Ikan Mujair Terhadap Sifat Organoleptik Abon Ampas Tahu Ikan Mujair (Abon Atm) - Lisda Juniarsy Rahardjo; Igde Narda Widiada; Reni Sofiyatin; Susilo Wirawan (Poltekkes Kemenkes Mataram, 2017)
Background. Abon is a dry food products with a crunchy textured and have a relatively long shelf life. Dregs tofu is the manufacture of solid waste out. Research Ridayanti, et al (2006) regarding the manufacture of shredded dregs tofu with dregs tofu formula of 50% and 50% addition of young jackfruit give organoleptic properties are preferred. Required the addition of a food that is rich in nutrients, easy to obtain, and have a low economic value of the chosen addition of tilapia fish. Research Wulandari (2007) is the substitution swordfish with tilapia fish in the manufacture of shredded much as 50% give organoleptic properties that are preferred by the panelists. Objective. To identify effect of adding Tilapia fish meat toward organoleptic properties (taste, smell, color, texture) of shredded dregs tofu tilapia fish. Research Methods. an experimental study design with a completely randomized design (CRD) one additional factor tilapia fish meat 10%, 30%, 50%, 70% and 90%. Treatment was repeated 3 times. The parameters observed organoleptic properties (color, smell, taste and texture). Data were analyzed using ANOVA. Research Result: Treatment t4 (70%) are most preferred in terms of color and taste, treatment t5 (90%) are most preferred in terms of smell, and treatment t2 (30%) are most preferred in terms of the texture of Abon ATM. Color obtain scores of panelists from 3.72 to 3.76, scores of smell 3.56 to 3.84, scores of taste from 3.42 to 3.72, and scores of texture from 3.64 to 3.96. The addition of tilapia fish meat no significant effect on the color, smell, and texture of Abon ATM (p>0,05) and significant effect on the taste of Abon ATM (p<0,05). Conclusions: The addition of tilapia fish meat significant effect on the taste of Abon ATM (p<0,05). The addition of Tilapia Fish meat 70% (t4) that is recommended.